Selected Problems and Positions on the Basis of Robophilosophy and Robotics - Musiał, Maciej (Sensus Historiae, 2022)
The purpose of this text is to discuss the main problems and positions present within one of the discourses dealing with the issue of robots, which is most often described as “robophilosophy” and “robot ethics.” In particular, the paper highlights the problems and positions that refer to the current and future impact of the growing presence of robots and attempts to diagnose and predict the range, intensity and significance of this impact, as well as its evaluation.